(untitled) (Research, Society and Development, 2025)
In Dentistry, many procedures are related to the recovery of tissue damage, especially in oral surgeries, which require surgical maneuvers such as incisions, detachments and manipulation of soft tissues, causing their discontinuity and the need for healing. The search for pain management in the post-surgical period is a constant objective of scholars on the subject, and there are currently several resources available to achieve this objective. Understanding the methods used to control postoperative pain in dental surgeries is part of the professional training of dentists, since it is a factor that is related to the success of the treatment. Therefore, understanding the pathophysiological mechanism of pain and conventional and adjuvant therapies is essential in clinical practice, being relevant for humanized treatment of patients. Given this reality, this study aims to identify the main conventional pharmacological and adjuvant therapies that effectively manage postoperative pain in dental surgeries, by conducting a state-of-the-art study on the subject, that is, developing a research that maps the academic productions on the subject and presents an overview of the subject. A literature review was carried out, through a search in scientific articles, books, case studies and bibliographic reviews published in a period of up to 10 years prior to the formulation of this study, in reliable sources and websites such as: PubMed, Google Scholar and SciELO.